Celestial Resistance - Maryia Rusak (Footprint)
The essay investigates the application of cosmotechnics in architecture through a case study of a large international construction venture, the Zambia World Bank Education Project. Financed in 1969 by the World Bank together with the Norwegian Agency for International Development (NORAD), the project envisioned the construction of sixty-five new secondary schools in under four years. A Norwegian consultancy company hired for the project proposed a modular semi-industrial building system and a computer-aided system of process management that defined the project’s cosmology. Not surprisingly, expectations of a new computerised modernity did not materialise, and the project was plagued by endless problems that seemed to be divine acts of resistance to which only celestial bodies could provide a solution. However, as this essay argues, these resistances can be considered sites of rupture, where the conflict between different cosmotechnics becomes apparent.  Based on original archival documents, the essay interrogates these resistances to universalist ideas of technology and ontological assumptions embedded and perpetuated through the architecture of post-colonial “development” projects. This study serves as a first stepping stone towards further investigations into how Western homogenising technologies could be negotiated and challenged for a more pluralistic technological paradigm.